Biochemical Changes of Three Cocoa Clones (Theobroma cacao L.) Under Drought Stress - Fakhrusy Zakariyya; Didik Indradewa (Jurnal Ilmu Pertanian, 2018)
Drought stress is a serious threat for cocoa production. One of the plant mechanisms to survive from the drought stress is through producing some biochemical compounds. The objective of this research was to know biochemical changes in three cocoa clones during drought stress. The research was conducted at the green house of Indonesian Coffee and Cocoa Research Institute from January – December 2017. The experiment was designed by using Randomized Complete Block Design (RCBD) with 2 factors and with 3 replications. The first factor was clones of scion that consisting KW 641, Sulawesi 1 and ICS 60 which each of its grafted to Scavina 6 clone as rootstock. The second factor was watering intervals which consisting; every 2 days / regularly watering (adequate of water), every 5 days (moderate drought), and every 8 days (severe drought). The result of this research showed that drought stress decreased chlorophyll content, increased hydrogen peroxide content (ROS), increased the activity of superoxide dismutation (SOD), increased ascorbic acid content, increased total phenolic content, and increased proline content. Sulawesi 1 and KW 641 clones showed lower hydrogen peroxide (ROS) content, while chlorophyll content, SOD activity, total phenolic content, ascorbic acid content, and proline content were higher compared with ICS 60 clone. It showed that Sulawesi 1 and KW 641 clones had more drought-resistance compared with ICS 60 clone.